Green fresh smoothie - some physico-chemical and nutritional aspects - Velciov Ariana (Proceedings of the International Symposium on Analytical and Environmental Problems, 2017)
Increasing tendency for fresh food - fruits, vegetables, and herbs consumption worldwide and also in our country, shows the weight that they have held or hold them in the diet. In their case, not only good looks, nice color or taste and aromas are considered to be important, but especially their nutritional value, rich in sugars, vitamins and minerals needed in the diet of the human body. They also have the advantage that it can be consumed without any processing who could reduce the nutritional value. The purpose of the study was to obtain and reveal some physico-chemical and nutritional properties of some fresh foods: green apple (Golden delicious – Malus domestica.), baby spinach (Spinach oleracea), pineapple (Ananas comosus) and mint leaves (Mentha piperita) and the juice that we obtain from them, while achieving a characterization highlighting their dietary and healing properties. The study presents important application not only for food industry, but also for other areas, because it addresses to special categories of consumers such as vegetarians and people with lactose intolerance and fasting period.